Leroy E. Cline, postcard to his Mother from France, March 14, 1919. - Auteur inconnu (Wikimedia Commons, 1919)
Notice image issue de Wikimedia Commons. Titre: Leroy E. Cline, postcard to his Mother from France, March 14, 1919.. These items were in a small cardboard box labeled: Mail from Leroy in war in France. Leroy E. Cline was born in Xenia, Ohio on February 20, 1893. He later lived in Columbus at 553 Hill Avenue. Leroy enlisted in the National Army on May 27, 1918. He served in the 4th Training Battalion, 158th Depot Brigade until June 17, 1918. He then transferred to the Mobile Ordnance Repair Shop and was a part of the American Expeditionary Forces from August 30, 1918 to May 6, 1919. He was given an honorable discharge on May 23, 1919. The Ordnance repair shops, camp U.S. Troops A.P.O 741, known as Atelier de Mehun-sur-Yevre, are located at the Village of Beauvoir, near the town of Mehun (Cher) on the main line of the P. & O. R. R., which has the main line of communication for the A.E.F.
Droits : Licence Public domain via Wikimedia Commons
Keywords: carte postale; image; patrimoine; architecture; histoire locale; Carte postale